INFECTOBESITY DAN PERIODONTITIS: HUBUNGAN DUA ARAH OBESITAS DAN PENYAKIT PERIODONTAL - I Komang Evan Wijaksana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: Obesity and periodontal diseases are two highly prevalent chronic conditions in Indonesia. Both obesity and periodontitis have been recognized as a major risk factor for a number of systemic diseases. Obesity related to the etiology and progression of periodontal disease was well known, but a recent study describes the role of periodontitis to obesity.Purpose: The aim of this article to explain possible bidirectional relationship of periodontitis and obesity, so that dental practitioners may play an important role in management both obesity and periodontal disease.Literature review: The concept of infectobesity refers to obesity of infectious origin was accepted for the possible role of oral bacteria in the development of obesity. Excessive storage of adipose tissue in obese individuals leads to the release of adipokines which produce inflammatory. Relentless release of pro-inflammatory cytokines into the systemic circulation from adipose tissue in obese individuals and periodontal bacteria and its product provides a systemic inflammatory overload and may be a reservoir for bidirectional relationship of periodontitis and obesity. Maintaining good oral health is also fundamental for obese individuals. Dental practitioners should play important role in managements by educate their obese patients and refer the patient to physician and dietitian for a proper maintaining obesity.Conc1usion: There is a bidirectional relationship between obesity ang periodontal disease.